Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Reconstructing prehistoric land cover and landuse in complex ‘blue-green’ landscapes - Kimberley L. Davies; M. Jane Bunting; Willem Koster; Nicki J. Whitehouse; Michelle Farrell; Henry Chapman; Jason R. Kirby; J. Edward Schofield; Phil Barratt; Benjamin Gearey; Nika Shilobod (Vegetation History and Archaeobotany, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

Strong genetic isolation despite wide distribution in a commercially exploited coastal shark - Kelvin L. Hull; Tamaryn A. Asbury; Charlene da Silva; Matthew Dicken; Ana Veríssimo; Edward D. Farrell; Stefano Mariani; Carlotta Mazzoldi; Ilaria A. M. Marino; Lorenzo Zane; Simo N. Maduna; Aletta E. Bester-van der Merwe (Hydrobiologia, 2019)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Diversity of demersal and megafaunal assemblages inhabiting sandbanks of the Irish Sea - Javier Atalah; Jayne Fitch; Jennifer Coughlan; Julien Chopelet; Ilaria Coscia; Edward Farrell (Marine Biodiversity, 2013)

Above- and belowground biomass measurements in an unthinned stand of Sitka spruce (Picea sitchensis (Bong) Carr.) - Carly Green; Brian Tobin; Michael O’Shea; Edward P. Farrell; Kenneth A. Byrne (European Journal of Forest Research, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Seasonal and spatial variability of soil respiration in four Sitka spruce stands - Gustavo Saiz; Carly Green; Klaus Butterbach-Bahl; Ralf Kiese; Valerio Avitabile; Edward P. Farrell (Plant and Soil, 2006)

Stand age‐related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH‐BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)
The effect of stand age on soil respiration and its components was studied in a first rotation Sitka spruce chronosequence composed of 10‐, 15‐, 31‐, and 47‐year‐old stands established on wet mineral gley in central Ireland. For each stand age, three forest stands with similar characteristics of soil type and site preparation were used. There were no significant differences in total soil respiration among sites of the same age, except for the case of a 15‐year‐old stand that had lower soil respiration rates due to its higher productivity. Soil respiration initially decreased with stand age, but levelled out in the older stands. The youngest stands had significantly higher respiration rates than more mature sites. Annual soil respiration rates were modelled by means of temperature‐derived functions. The average Q 10 value obtained treating all the stands together was 3.8. Annual soil respiration rates were 991, 686, 556, and 564 g C m −2 for the 10‐, 15‐, 31‐, and 47‐year‐old stands, respectively. We used the trenching approach to separate soil respiration components. Heterotrophic respiration paralleled soil organic carbon dynamics over the chronosequence, decreasing with stand age to slightly increase in the oldest stand as a result of accumulated aboveground litter and root inputs. Root respiration showed a decreasing trend with stand age, which was explained by a decrease in fine root biomass over the chronosequence, but not by nitrogen concentration of fine roots. The decrease in the relative contribution of autotrophic respiration to total soil CO 2 efflux from 59.3% in the youngest stand to 49.7% in the oldest stand was explained by the higher activity of the root system in younger stands. Our results show that stand age should be considered if simple temperature‐based models to predict annual soil respiration in afforestation sites are to be used.

Stand age-related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH-BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)